KiSo : a hybrid of a kitchen and sofa. - Tay, Esther Lee Ping. (2009)
Home is a place where we all return to rest and relax. However, being in a patriarch society, females are burden with dual roles- the role of the wife and that of the working woman. They will still have to prepare dinner after a day of work. Hence, much stress is induced with the responsibility of these roles. Therefore, it is common to find the wife busy preparing meals in the kitchen while the husband is watching television programmes in the living room.